Alternative splicing is coordinated through interconnected response pathways to direct major features of fungal cell physiology - João Neves-da-Rocha; Marcos E.R. Lopes; Mayara I.G. Azevedo; Monise F. Petrucelli; Maria J. Santos-Saboya; Antonio Rossi; Nilce M. Martinez-Rossi (Fungal Biology Reviews, 2026)

Streptomyces amazonensis sp. nov. isolated from Madeira river sediments with genomic potential for secondary metabolite production - Kiandro O. G. de Neves; Gerodes V. da Costa; Caio Cézar B. Campos; Claúdia A. Queiroz; Thiago F. Sousa; Aldenora S. dos Vasconcelos; Felipe M. A. da Silva; Michel Eduardo B. Yamagishi; Hector H. F. Koolen; Gilvan Ferreira da Silva (Brazilian Journal of Microbiology, 2026)
The genus Streptomyces is recognized as a source of secondary metabolites (SMs) with applications in medicine, industry, and agriculture. This study presents the description and characterization of a new Streptomyces species, isolated from sediments of the Madeira River in the Brazilian Amazon. Four strains (CPAA MAD 27, CPAA MAD 39, CPAA MAD 42, and CPAA MAD 51) were obtained from sampling sites distributed along the river. The strains were analyzed for morphological, phenotypic, and biochemical characteristics, as well as their potential for SM production using genome mining. Phylogenetic and phylogenomic analyses indicated that Streptomyces murinus is the most closely related species; however, the dDDH value of 55% and ANI of 94%, combined with biochemical analysis, support the proposal of the isolates as a new species, herein named Streptomyces amazonensis . This species exhibits adaptability to diverse environmental conditions, growing across a wide range of pH values (4–11) and temperatures (15–40 °C), with optimal growth at 35 °C and pH 8, and utilizing various carbon sources, including L-arabinose, unlike S. murinus . Genomic analysis revealed 39 to 46 biosynthetic gene clusters (BGCs) per strain, related to polyketides, nonribosomal peptides, and ribosomally synthesized and post-translationally modified peptides (RiPPs). Notably, BGCs showed high similarity to thioligamide (antitumor) and tetracenomycin (antibiotic) metabolites. Additionally, numerous BGCs with matches in the MIBiG database were identified, suggesting genomic potential related to the biosynthesis of molecules of scientific interest. This discovery expands our understanding of Amazonian microbial diversity and offers new prospects for the bioprospecting of natural products, highlighted by the unexplored biosynthetic potential of S. amazonensis for the development of new natural compounds.

Beyond rhodoliths: Community‐level carbon metabolism and calcification in coralline algal beds - Nadine Schubert; Fernando Tuya; Eduardo O. Bastos; Néstor E. Bosch; Paulo A. Horta; Julia Loring; André F. B. Macedo; Pedro Neves; Francisco Otero‐Ferrer; Viviana Peña; Cláudia Ribeiro; Rui Santos; et al. (Limnology and Oceanography, 2026)
Coastal ecosystems play a major role in global carbon cycling and storage, yet the contribution of calcifying macroalgal habitats, such as coralline algal beds (CABs; rhodolith and maerl beds), remains poorly understood. Because carbon cycling in CABs is governed by community productivity and calcification, which exert opposing effects on seawater carbonate chemistry, understanding the balance between these processes is essential for determining whether CABs function as net carbon sinks or sources. Yet, community‐level measurements remain scarce, and the environmental and biological drivers of CAB carbon balance are largely unknown. Here, we quantified net community productivity (NCP), net community calcification (NCC), and the resulting net carbon balance (NCP : NCC) in shallow warm‐temperate and subtropical Atlantic CABs with contrasting rhodolith‐associated communities, using in situ benthic chamber incubations. All CABs were net autotrophic, with NCP : NCC ratios ≥ 0.6, indicating that they acted as potentially carbon neutral and net carbon sinks. By combining our measurements with available community‐level datasets, we identified light availability as the primary environmental driver of community productivity and calcification, whereas benthic community structure influenced the balance between these processes. Together, our findings demonstrate that CAB carbon balance is governed by the interaction between environmental conditions and community structure, providing the first mechanistic insight into the drivers of ecosystem carbon balance. This pronounced context dependency highlights the need for community‐level assessments across broader environmental and biological settings to test the generality of these relationships and determine under which conditions carbon burial in CABs translates into a net contribution to coastal carbon storage.

Electrochemical strategies for lateral flow and LAMP-Based platforms toward pathogen detection: A critical review - Lucas F. de Lima; Paulo Felipe Neves Estrela; Leonardo Lopes-Luz; Lauro A. Pradela-Filho; Jonatas V. Souza; Daniel Júnior Almeida dos Santos; Gabriela R.M. Duarte; Wendell K.T. Coltro; Thiago R.L.C. Paixão (Analytica Chimica Acta, 2026)

Spatial Scale Modulates the Effect of Habitat Amount on Diversity Patterns of Arachnid Assemblages Across Different Brazilian Ecosystems - André F. A. Lira; Adriano M. DeSouza; Thayna R. Brito‐Almeida; Hugo L. L. Neves; Gilberto G. Rodrigues; Carlos Henrique De‐Oliveira‐Nogueira; Ubiratã F. Souza; Alessandra R. S. Andrade; Rafael G. Jansen; Ana Lúcia Tourinho; Leonardo S. Carvalho; Laís M. Pordeus; et al. (Journal of Biogeography, 2026)
Aim We evaluated how native vegetation cover influences the diversity of arachnid assemblages across multiple spatial scales in major Brazilian ecosystems. Location Brazil (Amazon and Atlantic rainforests, Cerrado savanna and Caatinga dry forest). Taxon Arachnida (Opiliones, Pseudoscorpiones and Scorpiones). Methods We sampled arachnids at 120 sites using active search and litter sifting. Native vegetation cover was quantified at three spatial scales (100, 200 and 300 m buffers) using GIS data. Assemblage structure was assessed using abundance, species richness, and Hill numbers ( q = 0, 1 and 2). Generalized linear mixed models were used to evaluate responses across taxonomic groups and ecosystems. Results We recorded 3986 individuals from 179 species. Diversity responses to native vegetation cover were taxon‐, ecosystem‐ and scale‐dependent. Positive effects of vegetation cover were stronger and more consistent in rainforest than in savanna and dry forest ecosystems. In rainforests, most responses occurred at smaller spatial scales (100–200 m), whereas no significant effects were detected in the savanna. Opiliones richness showed limited variation with vegetation cover but differed in dominance structure among ecosystems. Scorpion assemblages were characterized by low richness and high dominance, while pseudoscorpions exhibited low evenness in more species‐rich sites, particularly in the Amazon. Main Conclusions Native vegetation cover plays an important role in structuring arachnid diversity in Brazil, but its effects vary across taxa, ecosystems and spatial scales. These findings highlight the need for taxon‐ and scale‐specific conservation strategies and reinforce the importance of multi‐scale approaches to biodiversity conservation in Neotropical landscapes under increasing anthropogenic pressure.

Inclusion of carotenoids and Eicosapentaenoic Acid (EPA) in sea urchin (Paracentrotus lividus) broodstock diets improves gonad development and oocyte quality - A. S. Gomes; A. F. Rodrigues; M. Neves; C. Roseiro; H. Cardoso; A. P. Violante; P. J. Gavaia; C. Suckling; S. Lourenço (Aquaculture International, 2026)

Scientists’ warning on the global destruction of rock outcrop ecosystems - Luiza F. A. de Paula; Lucas N. Perillo; Gianluigi Ottaviani; Flávio F. Carmo; Mandar N. Datar; Katherine C. Enebeli‐Ekwutoziam; Bruno Fogliani; Stephen D. Hopper; Aboli Kulkarni; Hans Lambers; Rafael F. Magalhães; Frederico S. Neves; et al. (Conservation Biology, 2026)
Rock outcrops are geological formations that harbor a highly specialized biota adapted to harsh environmental conditions that differ from their surrounding landscapes. They are globally distributed, especially in old, highly weathered landscapes, and can function as habitat islands containing high levels of endemism and distinct evolutionary lineages. Despite their ecoevolutionary importance, rock outcrops remain largely overlooked in global conservation policy, ecosystem typologies, and biodiversity monitoring frameworks. Extractive activities directly remove the geological substrate that underpins these habitats, and climate change intensifies drought, heatwaves, and hydrological instability. Rising global demand for energy‐transition metals required for decarbonization is expected to further accelerate these pressures, particularly in biodiverse regions of the Global South where governance is weaker. Given that rock outcrop ecosystems are ecologically and evolutionarily significant, we devised a policy‐relevant conservation roadmap structured around prevention, mitigation, restoration, and governance issues. Priority actions include recognizing rock outcrops as unique ecosystems in global classifications and ecosystem typologies, integrating them into biodiversity monitoring frameworks, and improving the identification of key biodiversity areas and the International Union for Conservation of Nature (IUCN) Red List of Ecosystems assessments. We call for stronger environmental impact assessments, cumulative‐impact evaluations for mining and quarrying projects, and the designation of mining and quarrying exclusion sites of high irreplaceability. Coordinated international policy, improved ecological data, and meaningful engagement with local and Indigenous communities are essential to safeguard these ancient ecosystems before further, irreversible losses occur.

In vivo evaluation of the anti-inflammatory efficacy of liposomes loaded with Echinacea purpurea roots extracts - Sara F. Vieira; Diana Fonseca-Rodrigues; Daniel Mendanha; Vânia I. B. Castro; Ricardo A. Pires; Rui L. Reis; Filipa Pinto-Ribeiro; Helena Ferreira; Nuno M. Neves (Drug Delivery and Translational Research, 2026)
WHO ranked chronic inflammatory diseases as the most significant cause of death. The current therapeutic approach is the constant administration of clinically available anti-inflammatory drugs; however, this strategy presents severe side effects. New entities derived from plants have shown their potential for developing safe and effective therapies. Particularly, Echinacea purpurea extracts have demonstrated strong anti-inflammatory properties. Therefore, dichloromethanolic extracts of E. purpurea roots (DE-R), rich in alkylamides, were used to produce an anti-inflammatory formulation. To increase therapeutic efficacy, DE-R were loaded into liposomes (LPs), which were also engineered to actively target M1 macrophages via surface functionalization with folic acid (FLPs). The developed formulations were homogeneous, with a mean particle size of ≈114 nm. The liposomes were cytocompatible at all tested concentrations and strongly reduced IL-6 production in LPS-stimulated macrophages. As expected, FLPs + DE-R were 6.3 times better than LPs + DE-R, and 9.7 times greater than free DE-R. The anti-inflammatory activity of free DE-R and DE-R-loaded FLPs was assessed in an experimental rat model of inflammation. A single intra-articular injection of the FLPs + DE-R promoted a significant reduction of edema, inflammatory pain, and immune cell infiltration, particularly of CD68 + macrophages, as well as IL-6 expression. This formulation reduced synovial inflammation more efficiently than free DE-R. We also demonstrated that the developed formulation was safe, as no welfare changes or harmful toxicity to major organs were observed. Therefore, E. purpurea roots extracts loaded in liposomes can be used as a natural, innovative, and powerful new formulation to treat chronic inflammatory diseases. Graphical Abstract

Taxonomic uncertainty: causes, consequences, and metrics - Leila Meyer; Richard J. Ladle; Rafaela J. Trad; Annelise Frazão; Lívia Frateles; Thainá Lessa; Rafael B. Pinto; Tiago M.S. Freitas; Geiziane Tessarolo; Jhonny J.M. Guedes; Rodrigo A. Castro-Souza; Herison Medeiros; et al. (Trends in Ecology & Evolution, 2026)

Highly selective and reusable porphyrin-functionalized MCM-41 for efficient lead(II) removal from contaminated water: comprehensive adsorption study and real-water validation - Youssef Draoui; Smaail Radi; Mengmeng Wang; Amal El Mahdaoui; Chahrazad El Abiad; Aurelian Rotaru; Yann Garcia; M. Amparo F. Faustino; M. Graça P. M. S. Neves; Nuno M. M. Moura (Clean Technologies and Environmental Policy, 2026)

Impact of melatonin on inflammatory cytokine profiles in 24-hour cultured equine uterine explants’ - Murilo F. Rodrigues; Adriana P. Neves; Rogério Ferreira; Gilson A. Pessoa; Denise N. Araujo; Guilherme V. de Souza (Journal of Equine Veterinary Science, 2026)

New polymeric membranes containing mesoporous carbons doped with nitrogen and sulfur: A viable option for heavy metal removal from real electroplating effluents - Maria Vitória Rapôso Rodrigues; Natália Gabriele Camparotto; Anjaina F. de Albuquerque; Tauany de Figueiredo Neves; Olga Chernyayeva; Rafael L. Oliveira; Patrícia Prediger (Journal of Environmental Chemical Engineering, 2026)

Living and dead benthic foraminiferal assemblages as proxies for the environmental characterization in the mesotidal tropical estuary: Cachoeira River (Bahia, Brazil) - Lazaro Laut; Gabriel Camara; Kettollen Pereira; Pierre Belart; Luiz Fontana; Amanda Vilar; Paula T. Sardinha; Carla Bonetti; Maria Virginia Alves Martins; Silvia Helena M. Souza; Décio Semensatto; Sibelle T. Disaró; et al. (Environmental Monitoring and Assessment, 2026)

Quinolinium-substituted porphyrins as promising antimicrobial photosensitizers - Leticia D. Costa; Cátia Vieira; Mariana Q. Mesquita; Steffen Hackbarth; M. Graça P.M.S. Neves; Adelaide Almeida; Augusto C. Tomé; M. Amparo F. Faustino (Journal of Photochemistry and Photobiology B: Biology, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Modified proanthocyanidin DESIGNER materials with dentin biomodification activity - Shu-Xi Jing; Walleska Liberato; Guilherme Neves; James B. McAlpine; Shao-Nong Chen; Ana K. Bedran-Russo; Guido F. Pauli (Phytochemistry Letters, 2025)

Cytotoxicity of the benthic dinoflagellate Ostreopsis cf. ovata on coelomocytes of the green sea urchin Lytechinus variegatus - Raquel A.F. Neves; Clarissa Naveira; Silvia M. Nascimento; Wanderson F. Carvalho; Mariana Contins; Marcela R. Tavares; Luciano N. Santos (Marine Environmental Research, 2025)

3D-printed electrochemical loop-mediated isothermal amplification (E-LAMP): A miniaturized and portable platform to detect methicillin-resistant Staphylococcus aureus (MRSA) - Lucas F. de Lima; Paulo Felipe Neves Estrela; Lucas Costa Faustino; Jonatas V. Souza; Charleane Justino de Assunção; Everson T.S. Gerôncio; Leandro Fonseca de Lima; Elisa Flávia Luiz Cardoso Bailão; William R. de Araujo; Thiago R.L.C. Paixão; Gabriela R.M. Duarte (Analytica Chimica Acta, 2025)

HIV latency-reversing activity of latex from Euphorbia umbellata (Pax) Bruyns and three diterpenes isolated from this species - Gabrielle P. das Neves; José L. Mazzei; João B. F. Tostes; Marcos J. Nakamura; Helvécio V. A. Rocha; Pedro Junior P. Mourão; Amilcar Tanuri; Antonio J. Ribeiro da Silva; Antonio C. Siani (Natural Product Research, 2025)

Upregulation of NLRP3 Inflammasome in Specific Hippocampal Regions: Strengthening the Link Between Neuroinflammation and Selective Vulnerability in Alzheimer’s Disease - Eliana C. B. Toscano; Alberto F. O. Justo; Michelle C. A. Paula; Laura B. Grossi; Vitor H. Neves; Renata E. P. Leite; Vitor R. Paes; Rossana C. N. Melo; Ricardo Nitrini; Carlos Pasqualucci; Eduardo Ferriolli; Antonio L. Teixeira; et al. (Molecular Neurobiology, 2025)

Authentication of coriander oil and adulterant identification using electronic nose and spectroscopic techniques - Ingrid A. Moraes; Karine Cristine Kaufmann; Sylvio Barbon Junior; Marina G. Neves; Javier E.L. Villa; Douglas F. Barbin (Food Chemistry, 2025)

Ecological transcriptomics reveals stress response pathways of a ground‐herb species in a waterlogging gradient of Amazonian riparian forests - Clarisse Palma‐Silva; Amanda F. Mortati; Cleber Juliano Neves Chaves; Bárbara Simões Santos Leal; Rafael V. Ribeiro; Fabio Pinheiro; Milene Ferro; Diego M. Riaño‐Pachón; Jacqueline Salvi de Mattos; Marília Manupella Tavares; Paulo Aecyo; Tami da Costa Cacossi; et al. (Molecular Ecology, 2025)
Environmental stress is a fundamental facet of life and a significant driver of natural selection in the wild. Gene expression diversity may facilitate adaptation to environmental changes, without necessary genetic change, but its role in adaptive divergence remains largely understudied in Neotropical systems. In Amazonian riparian forests, species distribution is predominantly influenced by species' waterlogging tolerance. The flooding gradient delineates distinct wetland forest types, shaping habitats and species characteristics. Here we investigated the molecular basis of environmental stress response in a tropical ground‐herb species ( Ischnosiphon puberulus ) to environmental variation in Amazonian riparian forests. We compared environmental variables and gene expression profiles from individuals collected in two forest types: Igapó and Terra firme in the Amazonian riparian forests. Predictable seasonal flooding poses a significant challenge in Igapó compared to Terra firme environments, with the former presenting higher water column height and longer flooding duration. Our findings suggest that contrasting environmental conditions related to flooding regimes are important drivers of population genetic differentiation and differential gene expression in I. puberulus . Enriched gene ontology terms highlight associations with environmental stresses, such as defence response, water transport, phosphorylation, root development, response to auxin, salicylic acid and oxidative stress. By uncovering key environmental stress response pathways conserved across populations, I. puberulus offers novel genetic insights into the molecular basis of plant reactions to environmental constraints found in flooded areas of this highly biodiverse neotropical ecosystem.

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

Development of edible seaweed-based coating for postharvest preservation of mangoes - Manoely Virginia D.de B.S. Souza; Athaline G. Diniz; Valquíria Bruna Guimarães Silva; Maria Daniela S. Buonafina-Paz; José Ewerton F. dos Santos; Wêndeo K. Costa; Viviane L.X. de Souza Leão; Fálba B.R. dos Anjos; Wilson Barros Júnior; Rejane P. Neves; Patricia V. Tiago; Severino Alves Júnior (Biocatalysis and Agricultural Biotechnology, 2025)

Growth rates and ages of the small bamboo coral Acanella arbuscula in the Northwest Atlantic - Laura F. Piccirillo; Evan Edinger; Bárbara de Moura Neves; Meghan Burchell; Graham D. Layne; Vonda E. Hayes (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Corrigendum to “Aqueous compost extracts with stabilized biofertilizing microbiota promote plant root growth and drought resilience” [Sci. Total Environ. 974 (2025) 179157] - R. Lerma-Moliz; J. Hu; J.A. López-González; F. Suárez-Estrella; M.R. Martínez-Gallardo; M.M. Jurado; M.J. Estrella-González; A.J. Toribio; R. Jiménez; S. De Neve; M.J. López (Science of The Total Environment, 2025)

Tailoring selectivity and efficiency: pyrazolyl-1H-1,2,4-triazole MCM-41 and silica hybrid materials for efficient cadmium(II) removal from water - Youssef Draoui; Smaail Radi; Amal El Mahdaoui; Mohamed El Massaoudi; Aurelian Rotaru; Yann Garcia; Maria do Amparo F. Faustino; Maria da Graça P. M. S. Neves; Nuno M. M. Moura (Environmental Science and Pollution Research, 2025)
Two novel silica-based hybrid materials, M1 and M2 , based on silica gel and MCM-41 with a ditopic triazole-pyrazole ligand grafted onto their surfaces, respectively, were successfully synthesized and fully characterized. The adsorption capacity of these organic–inorganic hybrid materials was evaluated for copper(II), cadmium(II), and lead(II) ions. Experimental parameters including solution pH, contact time, temperature, and adsorbate concentration were systematically investigated. The obtained experimental data were analyzed using diverse adsorption isotherms and models to assess and interpret the behavior of the adsorbents. Notably, the newly synthesized materials exhibited exceptional selectivity, ultra-rapid adsorption rates within the first few minutes, and high removal efficiencies of 81.40 and 121.26 mg/g for M1 and M2 , respectively, towards Cd(II). Moreover, reusability assessments demonstrated excellent consistency, with only marginal decreases in adsorption capacities of less than 8% observed over five consecutive cycles. Interestingly, the application of M1 and M2 for the extraction of transition metals from real contaminated river water, from Nador city in Morocco, showcased their effectiveness in removing heavy metal ions even at low concentrations, with M2 achieving up to 67% cadmium removal. These findings highlight the potential of both materials as reliable systems for heavy metal removal in practical environmental remediation applications, with material M2 demonstrating superior performance over M1 . Graphical abstract

Aqueous compost extracts with stabilized biofertilizing microbiota promote plant root growth and drought resilience - R. Lerma-Moliz; J. Hu; J.A. López-González; F. Suárez-Estrella; M.R. Martínez-Gallardo; M.M. Jurado; M.J. Estrella-González; A.J. Toribio; R. Jiménez; S. De Neve; M.J. López (Science of The Total Environment, 2025)

Multistage emplacement of a composite intrusion: magnetic fabric and zircon U–Pb age of the Parnamirim Pluton, NE Brazil - C. H. F. S. Neves; S. P. Neves; V. P. Ferreira; A. N. Sial; B. T. A. Lima; D. H. Ardila; R. Siqueira (International Journal of Earth Sciences, 2025)

Cationic photosensitizers and potassium iodide: an innovative approach for enhanced photodynamic inactivation of pathogenic bacteria in aquaculture - Cátia Vieira; Maria Bartolomeu; Carlos J.P. Monteiro; Jesús L. Romalde; Pedro P. Gallego; M. Graça P.M.S. Neves; M. Amparo F. Faustino; Adelaide Almeida (Aquaculture, 2025)

Analysis of free-living seabirds from Brazil as potential hosts of Toxoplasma gondii and serological investigation for antibodies against Leptospira spp. - Igor C. L. Acosta; Daniela P. Chiebao; Patricia P. Serafini; Gabriel Canani; Hilda F. J. Pena; Marcos B. Heinemann; Antonio F. Souza-Filho; Cynthia Campolina; Caio A. Marques; Tatiana S. Neves; Marcio A. Efe; Guilherme T. Nunes; et al. (Veterinary Research Communications, 2025)

Plant-derived bioactive compounds as key players in the modulation of immune-related conditions - Sara F. Vieira; Rui L. Reis; Helena Ferreira; Nuno M. Neves (Phytochemistry Reviews, 2025)
The immune system is a complex and fundamental network for organism protection. A minimal unbalance in the host defense system homeostasis can originate severe repercussions in human health. Fundamentally, immune-related diseases can arise from its compromise (immunodeficiency diseases), overactivation against itself (autoimmune diseases) or harmless substances (allergies), and failure of eliminating the harmful agent (chronic inflammation). The notable advances and achievements in the immune system diseases pathophysiology have been allowing for a dramatic improvement of the available treatments. Nevertheless, they present some drawbacks, including the inappropriate benefit/risk ratio. Therefore, there is a strong and urgent need to develop effective therapeutic strategies. Nature is a valuable source of bioactive compounds that can be explored for the development of new drugs. Particularly, plants produce a broad spectrum of secondary metabolites that can be potential prototypes for innovative therapeutic agents. This review describes the immune system and the inflammatory response and examines the current knowledge of eight plants traditionally used as immunomodulatory medicines ( Boswellia serrata , Echinacea purpurea , Laurus nobilis , Lavandula angustifolia , Olea europaea , Salvia officinalis , Salvia rosmarinus , and Taraxacum officinale ). Moreover, the issues responsible for possible biologic readout inconsistencies (plant species, age, selected organ, developmental stage, growth conditions, geographical location, drying methods, storage conditions, solvent of extraction, and extraction method) will also be discussed. Furthermore, a detailed list of the chemical composition and the immunomodulatory mechanism of action of the bioactive compounds of the selected plant extracts are presented. This review also includes future perspectives and proposes potential new avenues for further investigation.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Lysine biosynthesis impairment gives cues about connection with TCA cycle intermediates in Arabidopsis response to salt disturbance - Tárik Galvão Neves; Débora Gonçalves Gouveia; Ítalo Antunes Pereira-Lima; Jessica A. S. Barros; Auxiliadora Oliveira Martins; Tamar Avin-Wittenberg; Adriano Nunes-Nesi; João Henrique F. Cavalcanti; Wagner L. Araújo (Theoretical and Experimental Plant Physiology, 2024)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

A multicommuted system using bacterial cellulose for urease immobilization and copper (II)-MOF colorimetric sensor for urea spectrophotometric determination in milk - Julyana C. Rodrigues; Caio S. Bezerra; Lidiane M.A. Lima; Danielle D. Neves; Ana Paula S. Paim; Wagner E. Silva; André F. Lavorante (Food Chemistry, 2024)

Construction and demolition waste as a low-cost adsorbent for water treatment: kinetics, isotherm, thermodynamics, and Fenton regeneration - Danilo H. S. Santos; Larissa F. Queiroz; Luiz D. Silva Neto; Keven E. Santos; Denio D. C. S. das Neves; Anamália F. Silva; Eduardo J. S. Fonseca; Daniel P. Fernandes; Lucas Meili (Environmental Science and Pollution Research, 2024)

Progress in the modification of cellulose-based adsorbents for the removal of toxic heavy metal ions - Amal El Mahdaoui; Smaail Radi; Abderrahman Elidrissi; M. Amparo F. Faustino; M. Graça P.M.S. Neves; Nuno M.M. Moura (Journal of Environmental Chemical Engineering, 2024)

Subchronic intake of arsenic at environmentally relevant concentrations causes histological lesions and oxidative stress in the prostate of adult Wistar rats - John L.P. Coimbra; Gabriel Campolina-Silva; Daniel F. Lair; Luiz O. Guimarães-Ervilha; Ana C.F. Souza; Cleida A. Oliveira; Guilherme M.J. Costa; Mariana Machado-Neves (Reproductive Toxicology, 2024)

Orthohantavirus infections in South America: a systematic review and meta-analysis - Sílvia C.S. Oloris; Valquíria F. Neves; Felipe C.M. Iani; Cristiane Faria de Oliveira Scarponi (Archives of Virology, 2024)

Wastewater disinfection with photodynamic treatment and evaluation of its ecotoxicological effects - Maria Bartolomeu; Thierry J. Gomes; Fábio Campos; Cátia Vieira; Susana Loureiro; M. Graça P.M.S. Neves; M. Amparo F. Faustino; Ana T.P.C. Gomes; Adelaide Almeida (Chemosphere, 2024)

Anomaly detection in hydrological network time series via multiresolution analysis - Jorge A. Pimentel Filho; Claudio F. Neves; Walszon T.A. Lopes; João Carlos Carvalho (Journal of Hydrology, 2024)

A biofloc system avoids the adverse effects of diets with suboptimal protein levels on zootechnical performance, intestinal histomorphometry, and protein metabolism of Nile tilapia juvenile fed Spirulina biomass (Arthrospira platensis) as an alternative protein source - Fernanda Picoli; Alana D. de Oliveira; Suelyn O. Marques; Deise C. Terhorst; Suélen Serafini; Luísa Nora; Fabio F. Neves; Maurício G. C. Emerenciano; Diogo L. A. Lopes; Aleksandro S. da Silva; Thiago E. H. P. Fabregat (Fish Physiology and Biochemistry, 2024)

Beta diversity and regionalization of the western Atlantic marine biota - Ubirajara Oliveira; Fernanda Azevedo; Alan Dias; Ana Carolina Sousa de Almeida; André R. Senna; Antonio C. Marques; Dafinny Rezende; Eduardo Hajdu; Erick Alves Pereira Lopes‐Filho; Fábio Bettini Pitombo; Gabriela Moura de Oliveira; João Gabriel Doria; et al. (Journal of Biogeography, 2024)
Aim Understanding the factors determining marine community variations is important for biogeography and conservation. Beta diversity is a metric for mapping species composition variations between communities and regionalizing biota. Ecoregions are commonly used for regionalization, but their empirical testing has been limited. Our aim is to map marine species composition variations in the Western Atlantic, identify variables related to these variations, and regionalize areas based on community distribution. Additionally, we test whether currently proposed ecoregions represent unique biota units and specific environmental conditions. Location Western Atlantic Ocean. Taxon Vertebrates, invertebrates and algae. Methods We constructed a large marine biodiversity database, including vertebrates, invertebrates, and algae, totalling over 4 million records. We used the generalized dissimilarity model (GDM) to identify variables most related to species composition variations and map beta‐diversity variations. We employed an unsupervised classifier for community regionalization. To test if the ecoregion regionalization boundaries are corroborated by species distribution data, we used the Sørensen index. To assess if ecoregions correspond to environmental units, we checked if areas had distinct environmental conditions using a PCA of 134 marine environmental variables. Results The GDM explained a high variation in species composition, 61% in the complete database. Analysing vertebrates, invertebrates and algae separately also yielded relatively high results: 46%, 54%, and 33%, respectively. Coastal areas differed from open sea areas in composition. Environmental variables combined better explained beta diversity than isolated variables. The regionalization based on GDM was not congruent with ecoregion boundaries. Moreover, ecoregions showed no distinction in species composition or environmental conditions. Main Conclusions This study's regionalization is crucial for marine biodiversity conservation, focusing on understanding species composition patterns between coastal and open sea areas to develop tailored conservation strategies. Despite sampling limitations, the study advances marine biogeography knowledge by analysing over 4 million species records and 134 environmental variables. This comprehensive approach enhances understanding marine species distribution and diversity and aiding the development of effective conservation measures.

Impact of reducing lipid content during in vitro embryo production: A systematic review and meta-analysis - Erlandia M. Vasconcelos; Rachel F. Braga; Gabriela R. Leal; Renner P.R. Carvalho; Mariana Machado-Neves; Mateus J. Sudano; Joanna M.G. Souza-Fabjan (Theriogenology, 2024)

Evidence of plastics contamination and sewage-derived residues in a Brazilian Hope Spot for conservation of marine biodiversity - Cagarras Islands and surrounding waters - Raquel A.F. Neves; Nathália Rodrigues; Guilherme de Luca; Maria Alene A. Oliveira; Thuany F. Carvalho; Nicole S. Santos; Maria Eduarda S. Adelino; Luiza Belli Caldas; Agatha Miralha; Clarissa Naveira; Antonio J.S. Rodrigues; Igor C. Miyahira; et al. (Marine Pollution Bulletin, 2024)

Congenital right atrial diverticulum in a kitten - B. Pedro; F. Sarcinella; C. Linney; J. Neves; L. Mesquita (Journal of Veterinary Cardiology, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Exploiting the therapeutic potential of contracting skeletal muscle-released extracellular vesicles in cancer: Current insights and future directions - Ana Carolina Pinto; Patrícia Tavares; Bruno Neves; Pedro F. Oliveira; Rui Vitorino; Daniel Moreira-Gonçalves; Rita Ferreira (Journal of Molecular Medicine, 2024)
The health benefits of exercise training in a cancer setting are increasingly acknowledged; however, the underlying molecular mechanisms remain poorly understood. It has been suggested that extracellular vesicles (EVs) released from contracting skeletal muscles play a key role in mediating the systemic benefits of exercise by transporting bioactive molecules, including myokines. Nevertheless, skeletal muscle-derived vesicles account for only about 5% of plasma EVs, with the immune cells making the largest contribution. Moreover, it remains unclear whether the contribution of skeletal muscle-derived EVs increases after physical exercise or how muscle contraction modulates the secretory activity of other tissues and thus influences the content and profile of circulating EVs. Furthermore, the destination of EVs after exercise is unknown, and it depends on their molecular composition, particularly adhesion proteins. The cargo of EVs is influenced by the training program, with acute training sessions having a greater impact than chronic adaptations. Indeed, there are numerous questions regarding the role of EVs in mediating the effects of exercise, the clarification of which is critical for tailoring exercise training prescriptions and designing exercise mimetics for patients unable to engage in exercise programs. This review critically analyzes the current knowledge on the effects of exercise on the content and molecular composition of circulating EVs and their impact on cancer progression.

Molecular Verification of Trichophyton in the Brazilian URM Culture Collection - Tatiana F. Oliveira; Carlos A. T. Valeriano; M. Daniela S. Buonafina-Paz; Cristina M. Souza-Motta; Alexandre R. Machado; Rejane P. Neves; Jadson D. P. Bezerra; Thales D. Arantes; Sybren de Hoog; Oliane M. C. Magalhães (Mycopathologia, 2024)

Spatial and temporal abilities of proxies used to detect pre-Columbian Indigenous human activity in Amazonian ecosystems - C.N.H. McMichael; C. Levis; W.D. Gosling; A.B. Junqueira; D.R. Piperno; E.G. Neves; F. Mayle; M. Peña-Claros; F. Bongers (Quaternary Science Reviews, 2023)

Fatigue life estimate of metallic chain links of mooring systems assuming out of plane bending: From constant amplitude to random loading - L. de Oliveira Barros; F. Aguiar Hansen; R. Silva Neves; G. Vaz Ferreira; L.L. Delgado Morales; L. Malcher (Ocean Engineering, 2023)

Official veterinarians in Europe: Questionnaire-based insights into demographics, work and training - Eduarda Gomes-Neves; Margarida F. Cardoso; Thomai Lazou; Brigita Hengl; Silvia Bonardi; Bojan Blagojevic; Claudia Guldiman; Sophia Johler (Food Control, 2023)

Comparing morphological and secretory aspects of cephalic glands among the New World coral snakes brings novel insights on their biological roles - Leonardo de Oliveira; Pedro Gabriel Nachtigall; Vincent Louis Vialla; Pollyanna F. Campos; Adriana da Costa-Neves; Hussam Zaher; Nelson Jorge da Silva Jr.; Felipe G. Grazziotin; Mark Wilkinson; Inácio L.M. Junqueira-de-Azevedo (Toxicon, 2023)

Refinements in embryo manipulation applied to CRISPR technology in livestock - P.C. dos Santos-Neto; F. Cuadro; M. Souza-Neves; M. Crispo; A. Menchaca (Theriogenology, 2023)

Levelling-up rhodolith-bed science to address global-scale conservation challenges - Fernando Tuya; Nadine Schubert; Julio Aguirre; Daniela Basso; Eduardo O. Bastos; Flávio Berchez; Angelo F. Bernardino; Néstor E. Bosch; Heidi L. Burdett; Fernando Espino; Cindy Fernández-Gárcia; Ronaldo B. Francini-Filho; et al. (Science of The Total Environment, 2023)

Starch-based films doped with porphyrinoid photosensitizers for active skin wound healing - Paloma Lopes; A. Sofia M. Joaquinito; Artur Ribeiro; Nuno M.M. Moura; Ana T.P. Gomes; Susana G. Guerreiro; M. Amparo F. Faustino; Adelaide Almeida; Paula Ferreira; Manuel A. Coimbra; M. Graça P.M.S. Neves; Idalina Gonçalves (Carbohydrate Polymers, 2023)

Porphyrin-silica gel hybrids as effective and selective copper(II) adsorbents from industrial wastewater - Chahrazad El Abiad; Smaail Radi; Mohamed El Massaoudi; Morad Lamsayah; Flávio Figueira; M. Amparo F. Faustino; M. Graça P.M.S. Neves; Nuno M.M. Moura (Journal of Environmental Chemical Engineering, 2023)

Geochemical behavior of rare earth elements (REE) in urban reservoirs: the case of Funil Reservoir, Rio de Janeiro State, Brazil - J. M. C. O. Santos-Neves; S. R. Patchineelam; D. F. Araujo; J. M. O. Godoy; A. C. Almeida (Environmental Monitoring and Assessment, 2023)

Hypereutrophic conditions limit the removal of suspended particulate matter by the invasive bivalve Mytilopsis leucophaeata (Conrad, 1831) (Dreissenidae) - Nathália Rodrigues; Danielle Ribeiro; Igor C. Miyahira; Samira G. M. Portugal; Luciano N. Santos; Raquel A. F. Neves (Hydrobiologia, 2023)

Photodynamic inactivation of microorganisms in different water matrices: The effect of physicochemical parameters on the treatment outcome - Maria Bartolomeu; Carlos J.P. Monteiro; Milton Fontes; Maria Graça P.M.S. Neves; Maria Amparo F. Faustino; Adelaide Almeida (Science of The Total Environment, 2023)

Essential oil and residual distillation water of Pterocaulon polystachyum DC: composition, antifungal activity, and mathematical modeling of steam distillation - Júlia M. Scopel; Bruna Medeiros-Neves; Helder Teixeira; Sérgio A.L Bordignon; Alexandre M. Fuentefria; Gabriella da Rosa Monte Machado; Rafael N. Almeida; Eduardo Cassel; Gilsane L. von Poser; Rubem M. F. Vargas (Plant Biosystems, 2022)

Structural analysis of the peptides temporin-Ra and temporin-Rb and interactions with model membranes - José L. S. Lopes; Caio C. F. Araujo; Rogério C. Neves; Jochen Bürck; Sheila G. Couto (European Biophysics Journal, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Wide tolerance to environmental conditions and substrate colonization mediates the invasion of false mussels (Bivalvia: Dreissenidae) in brackish systems - Antonio J. S. Rodrigues; Igor C. Miyahira; Nathália Rodrigues; Danielle Ribeiro; Luciano N. Santos; Raquel A. F. Neves (Biological Invasions, 2022)

Should local drug delivery systems be used in dentistry? - Joana Vieira Costa; Jaime Portugal; Cristina Bettencourt Neves; Ana F. Bettencourt (Drug Delivery and Translational Research, 2022)

Identification of Glycycometus malaysiensis (for the first time in Brazil), Blomia tropicalis and Dermatophagoides pteronyssinus through multiplex PCR - Vítor S. Alves; Luis F. Salazar-Garcés; Leonardo F. Santiago; Paula L. C. Fonseca; Antônio M. S. Fernandes; Raphael C. Silva; Lorena M. Souza; Pedro P. R. S. Cunha; Marina F. C. Barbosa; Eric R. G. R. Aguiar; Luis G. C. Pacheco; Neuza M. Alcantara-Neves; et al. (Experimental and Applied Acarology, 2022)

A comparison of stereo-videos and visual census methods for assessing subtropical rocky reef fish assemblage - Fernanda A. Rolim; Pedro F. C. Rodrigues; Tim Langlois; Leonardo M. Neves; Otto B. F. Gadig (Environmental Biology of Fishes, 2022)

Leucoagaricus taniae sp. nov. (Agaricaceae), a sand-dwelling mushroom from Brazil - Celeste Heisecke; Duane F. Lima; Gregory M. Mueller; Maria Alice Neves (Brittonia, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Short-term effects of very heavy rainfall events on the water quality of a shallow coastal lagoon - Raquel A. F. Neves; Luciano N. Santos (Hydrobiologia, 2021)

Harmful algal blooms and shellfish in the marine environment: an overview of the main molluscan responses, toxin dynamics, and risks for human health - Raquel A. F. Neves; Silvia M. Nascimento; Luciano N. Santos (Environmental Science and Pollution Research, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Coastal Ocean Observing and Modeling Systems in Brazil: Initiatives and Future Perspectives - Guilherme Franz; Carlos A. E. Garcia; Janini Pereira; Luiz Paulo de Freitas Assad; Marcelo Rollnic; Luis Hamilton P. Garbossa; Letícia Cotrim da Cunha; Carlos A. D. Lentini; Paulo Nobre; Alexander Turra; Janice R. Trotte-Duhá; Mauro Cirano; et al. (Frontiers in Marine Science, 2021)
Coastal ocean observing and modeling systems (coastal observatories), connected with regional and global ocean systems, improve the quality of information and forecasts for effective management of safe and sustainable maritime activities. The public availability of systematic and long-term information of the ocean is an engine for the Blue Economy, boosting economic growth, employment, and innovation. An overview of some Brazilian initiatives is presented in this paper, involving universities, private companies, federal and state agencies, covering institutions from south to north of Brazil. Although these initiatives focus mainly on ocean physics, integrated efforts can extend the scope to include biogeochemistry and marine biodiversity, helping to address interdisciplinary problems. Existing initiatives can be connected, and new ones fostered, to fill in the gaps of temporal and spatial coverage of ocean monitoring in the vast oceanic area under Brazilian jurisdiction (nationally referred to as the Blue Amazon, in reference to the similar richness of the Amazon Forest). The alignment among national and regional initiatives, as well as with international programs, can be promoted if coordinated by a national-level organization, maximizing the return of public investment and socioeconomic benefits. In light of international examples, possible future institutional arrangements are discussed, leveraging from existing national public policies and international cooperation that Brazil is taking part. The United Nations Decade of Ocean Science for Sustainable Development is a timely opportunity to encourage an institutional arrangement to support and articulate an integrated network of coastal observatories in Brazil.

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Quality Indexes and Performance in Mechanized Harvesting of Sugarcane at a Burnt Cane and Green Cane - Marcelo J. da Silva; Lucas de O. Neves; Murilo H. F. Correa; Carlos H. W. de Souza (Sugar Tech, 2021)

The drifting dinoflagellate Ceratium furcoides (Levander) Langhans 1925: fundamental niche shift during global invasion - Rafael Lacerda Macêdo; Philip Russo; Raphael F. Corrêa; Odete Rocha; Luciano Neves dos Santos; Christina W. C. Branco (Hydrobiologia, 2021)

Using richness of native and non-native aquatic species along a climatic gradient to test the intermediate disturbance hypothesis - Luciano N. Santos; Ana Clara S. Franco; Joice S. de Souza; Igor C. Miyahira; Antonio Jailson S. Rodrigues; Isabela Cristina B. Gonçalves; Natascha Krepsky; Helga A. B. Monte; Clarissa Naveira; Tatiana M. B. Cabrini; Rayane R. S. Abude; Matheus Augusto; et al. (Hydrobiologia, 2021)

Whole body vibration influence on bus fare collectors evaluated by using a brain training mobile app - S. G. Firmino; M. L. M. Duarte; J. A. B. Neves; P. A. X. Viana; F. S. B. de Araújo (International Archives of Occupational and Environmental Health, 2021)

Dihydroquinoline derivative as a potential anticancer agent: synthesis, crystal structure, and molecular modeling studies - W. F. Vaz; J. M. F. Custodio; G. D. C. D’Oliveira; B. J. Neves; P. S. C. Junior; J. T. M. Filho; C. H. Andrade; C. N. Perez; E. P. Silveira-Lacerda; H. B. Napolitano (Molecular Diversity, 2021)

A letter to my climate change skeptical neighbor: some thoughts about the coastal zone - Claudio F. Neves (Geo-Marine Letters, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The life and times of yeasts in traditional food fermentations - Rosanna Tofalo; Vincenzina Fusco; Christina Böhnlein; Jan Kabisch; Antonio F. Logrieco; Diana Habermann; Gyu-Sung Cho; Nabil Benomar; Hikmate Abriouel; Markus Schmidt-Heydt; Horst Neve; Wilhelm Bockelmann; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Influence of Deep-Water Corals and Sponge Gardens on Infaunal Community Composition and Ecosystem Functioning in the Eastern Canadian Arctic - Marie Pierrejean; Cindy Grant; Bárbara de Moura Neves; Gwénaëlle Chaillou; Evan Edinger; F. Guillaume Blanchet; Frédéric Maps; Christian Nozais; Philippe Archambault (Frontiers in Marine Science, 2020)

A General Methodology for Beached Oil Spill Hazard Mapping - Antonio A. Sepp Neves; Nadia Pinardi; Antonio Navarra; F. Trotta (Frontiers in Marine Science, 2020)

Deep genetic divergence and paraphyly in cryptic species of Mugil fishes (Actinopterygii: Mugilidae) - Jessika M. M. Neves; JoÃo P. F. A. Almeida; Marcelo J. Sturaro; Nidia N. FabrÉ; Ricardo J. Pereira; TamÍ Mott (Systematics and Biodiversity, 2020)

Drivers of bromeliad leaf and floral bract variation across a latitudinal gradient in the Atlantic Forest - Beatriz Neves; Camila M. Zanella; Igor M. Kessous; Fernando P. Uribbe; Fabiano Salgueiro; Fernanda Bered; Alexandre Antonelli; Christine D. Bacon; Andrea F. Costa (Journal of Biogeography, 2020)
Aim Understanding the complex interaction and relative contributions of factors involved in species and trait diversification is crucial to gain insights into the evolution of Neotropical biodiversity. Here, we investigated the drivers of morphological variation in bromeliads along a latitudinal gradient in a biodiversity hotspot. Location Atlantic Forest, Brazil. Taxon A species complex in the genus Vriesea (Bromeliaceae). Methods We measured shape and size variation for 208 floral bracts and 176 leaves in individuals from 14 localities using geometric morphometrics. We compiled data for two chloroplast regions ( matK and trnL‐F ) from 89 individuals to assess genetic diversity, population structure and phylogenetic relationships. We tested the influence of climate, altitude and genetic distance on morphological traits using linear statistical models. Results Temperature seasonality is a main driver of floral bract shape. Together with precipitation, it also explains changes in leaf size across the latitudinal gradient. Shifts in morphological traits are correlated with genetic structure and partly support the recent taxonomic delimitation proposed for the species complex. The species started to diversify in the Pliocene ca. 5 Mya. We detected a phylogeographical break in species distribution into northern and southern clades between the Bocaina region and the southern portion of the Atlantic Forest. Main Conclusions We identify how geography and environmental changes through time shape floral bracts and leaves in similar ways. At highly seasonal sites with lower annual precipitation (in the southern subtropical portion of the Atlantic Forest), leaves are larger and floral bracts are wide‐elliptic, making them better suited for increased water accumulation. In contrast, at less seasonal sites (in the tropical north, where rainfall is more abundant and temperatures are higher), leaves are narrower and floral bracts are lanceolate‐shaped, facilitating water drainage. The biogeographical break we identified suggests a role of tectonic activity and climatic oscillations in promoting species divergence and diversification.

Intraspecific Cuticular Chemical Profile Variation in the Social Wasp Mischocyttarus consimilis (Hymenoptera, Vespidae) - E. F. Neves; L. D. Lima; D. Sguarizi-Antonio; L. H. C. Andrade; S. M. Lima; S. E. Lima-Junior; W. F. Antonialli-Junior (Neotropical Entomology, 2019)

The Retina as a Window or Mirror of the Brain Changes Detected in Alzheimer’s Disease: Critical Aspects to Unravel - Samuel Chiquita; Ana C. Rodrigues-Neves; Filipa I. Baptista; Rafael Carecho; Paula I. Moreira; Miguel Castelo-Branco; António F. Ambrósio (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Use of Low Temperature Storage to Preserve Host and Parasitoid to Improve the Rearing of Telenomus podisi (Hymenoptera: Platygastridae) on Euschistus heros (Hemiptera: Pentatomidae) Eggs - G V Silva; A F Bueno; B M Favetti; P M O J Neves (Neotropical Entomology, 2019)

Variable rate spraying application on cotton using an electronic flow controller - F. H. R. Baio; D. C. Neves; H. B. Souza; A. J. F. Leal; R. C. Leite; J. P. Molin; S. P. Silva (Precision Agriculture, 2018)

First report of Fusarium lacertarum causing cladode rot in Nopalea cochenellifera in Brazil - Michele F. Santiago; Alice M. G. Santos; Cícero P. Inácio; Amaro C. Lira Neto; Tereza C. Assis; Rejane P. Neves; Vinson P. Doyle; Josiene S. Veloso; Willie A. S. Vieira; Marcos P. S Câmara; Delson Laranjeira (Journal of Plant Pathology, 2018)

The Effects of Fillers and Binders on the Accuracy of Tablet Subdivision - Gessyka Rayana S. Pereira; Stephania F. Taveira; Marcilio Cunha-Filho; Ricardo Neves Marreto (AAPS PharmSciTech, 2018)

Photoinactivation of Pseudomonas syringae pv. actinidiae in kiwifruit plants by cationic porphyrins - Diana Martins; Mariana Q. Mesquita; Maria G. P. M. S. Neves; Maria A. F. Faustino; Luís Reis; Etelvina Figueira; Adelaide Almeida (Planta, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

How Bad Is Aluminum Exposure to Reproductive Parameters in Rats? - Viviane G. S. Mouro; Tatiana P. Menezes; Graziela D. A. Lima; Rafael R. Domingues; Ana Cláudia F. Souza; Juraci A. Oliveira; Sérgio L. P. Matta; Mariana Machado-Neves (Biological Trace Element Research, 2018)

Use of formalin in intensive aquaculture: properties, application and effects on fish and water quality - Joana F. Leal; Maria Graça P. M. S. Neves; Eduarda B. H. Santos; Valdemar I. Esteves (Reviews in Aquaculture, 2018)
Formalin (aqueous solution of formaldehyde stabilized with methanol) is one of the most used disinfectants in aquaculture. It is used to eliminate infectious agents but may be responsible for negative effects on fish and water quality. This work focuses on physical–chemical properties of formalin and on its reactions and its use in intensive aquaculture and in environment. The types of treatments and the action mode of formalin are also described. The main consequences of formalin exposure to fish are damage in gills and alterations in mucous cells. Formalin also interacts with some treatments adopted in aquaculture establishments, for example biological filter, where the nitrification process seems to be strongly affected. With respect to formalin inactivation, formaldehyde (effluent) may be diluted with water or specific treatments should be conducted to decrease the concentration levels before its discharge into the environment. The common methodologies applied to aquaculture are not completely efficient on formalin removal from water, and the advanced oxidation processes may be a good alternative.

On the Adult Behavioral Repertoire of the Sawfly Perreyia flavipes Konow, 1899 (Hymenoptera: Pergidae): Movement, Mating, and Thanatosis - F M Neves; M R Pie (Neotropical Entomology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice - Fernanda S. Neves; Patrícia T. Marques; Fernanda Barros‑Aragão; José Bruno Nunes; Aline M. Venancio; Danielle Cozachenco; Rudimar L. Frozza; Giselle F. Passos; Robson Costa; Jade de Oliveira; Daiane F. Engel; Andreza F. De Bem; et al. (Molecular Neurobiology, 2018)

Rhipicephalus microplus (Acarina, Ixodidae) in Angola: evidence of its establishment and expansion - Adriano F. Gomes; Luis Neves (Experimental and Applied Acarology, 2018)

Seabird mortality induced by land‐based artificial lights - Airam Rodríguez; Nick D. Holmes; Peter G. Ryan; Kerry‐Jayne Wilson; Lucie Faulquier; Yovana Murillo; André F. Raine; Jay F. Penniman; Verónica Neves; Beneharo Rodríguez; Juan J. Negro; André Chiaradia; et al. (Conservation Biology, 2017)
Artificial lights at night cause high mortality of seabirds, one of the most endangered groups of birds globally. Fledglings of burrow‐nesting seabirds, and to a lesser extent adults, are attracted to and then grounded (i.e., forced to land) by lights when they fly at night. We reviewed the current state of knowledge of seabird attraction to light to identify information gaps and propose measures to address the problem. Although species in families such as Alcidae and Anatidae can be grounded by artificial light, the most affected seabirds are petrels and shearwaters (Procellariiformes). At least 56 species of Procellariiformes, more than one‐third of them (24) threatened, are subject to grounding by lights. Seabirds grounded by lights have been found worldwide, mainly on oceanic islands but also at some continental locations. Petrel breeding grounds confined to formerly uninhabited islands are particularly at risk from light pollution due to tourism and urban sprawl. Where it is impractical to ban external lights, rescue programs of grounded birds offer the most immediate and employed mitigation to reduce the rate of light‐induced mortality and save thousands of birds every year. These programs also provide useful information for seabird management. However, these data are typically fragmentary, biased, and uncertain and can lead to inaccurate impact estimates and poor understanding of the phenomenon of seabird attraction to lights. We believe the most urgently needed actions to mitigate and understand light‐induced mortality of seabirds are estimation of mortality and effects on populations; determination of threshold light levels and safe distances from light sources; documentation of the fate of rescued birds; improvement of rescue campaigns, particularly in terms of increasing recovery rates and level of care; and research on seabird‐friendly lights to reduce attraction.

Testing the usefulness of hydrogen and compound-specific stable isotope analyses in seabird feathers: a case study in two sympatric Antarctic storm-petrels - Petra Quillfeldt; Simon Thorn; Benjamin Richter; Marcela Nabte; Nestor Coria; Juan F. Masello; Melanie Massaro; Verónica C. Neves; Marcela Libertelli (Marine Biology, 2017)

The extraction and characterisation of a polysaccharide from Moniliophthora perniciosa CCMB 0257 - Gildomar L. Valasques Junior; Elisangela F. Boffo; Jener David G. Santos; Hugo Neves Brandão; Artur J. S. Mascarenhas; Fernanda T. Cruz; Sandra A. Assis (Natural Product Research, 2017)

Expression of the citrus CsTIP2;1 gene improves tobacco plant growth, antioxidant capacity and physiological adaptation under stress conditions - Cristina P. S. Martins; Diana M. Neves; Luciana C. Cidade; Amanda F. S. Mendes; Delmira C. Silva; Alex-Alan F. Almeida; Mauricio A. Coelho-Filho; Abelmon S. Gesteira; Walter S. Soares-Filho; Marcio G. C. Costa (Planta, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

Selection and Characterization of Bacillus thuringiensis (Berliner) (Eubacteriales: Bacillaceae) Strains for Ecdytolopha aurantiana (Lima) (Lepidoptera: Tortricidae) Control - J Zorzetti; A P S Ricietto; F A P Fazion; A M Meneguim; P M O J Neves; L A Vilas-Boas; R B Rodrigues; G T Vilas-Bôas (Neotropical Entomology, 2017)

Up-Regulation of Oligodendrocyte Lineage Markers in the Cerebellum of Autistic Patients: Evidence from Network Analysis of Gene Expression - Fares Zeidán-Chuliá; Ben-Hur Neves de Oliveira; Manuel F. Casanova; Emily L. Casanova; Mami Noda; Alla B. Salmina; Alexei Verkhratsky (Molecular Neurobiology, 2016)

Effects of algal mats on a tropical estuarine benthic system: sediment biogeochemistry and macrofauna - Ana P. M. C. Valença; Caroline C. C. Clemente; Julia R. Neves; Janilson F. Silva; Ranilson S. Bezerra; Mônica L. Botter-Carvalho; Paulo V. V. C. Carvalho; Paulo J. P. Santos (Hydrobiologia, 2016)

Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Fernando A. O. Silveira; Daniel Negreiros; Newton P. U. Barbosa; Elise Buisson; Flávio F. Carmo; Daniel W. Carstensen; Abel A. Conceição; Tatiana G. Cornelissen; Lívia Echternacht; G. Wilson Fernandes; Queila S. Garcia; Tadeu J. Guerra; et al. (Plant and Soil, 2016)

Axonal elongation and dendritic branching is enhanced by adenosine A2A receptors activation in cerebral cortical neurons - Filipa F. Ribeiro; Raquel Neves-Tomé; Natália Assaife-Lopes; Telma E. Santos; Rui F. M. Silva; Dora Brites; Joaquim A. Ribeiro; Mónica M. Sousa; Ana M. Sebastião (Brain Structure and Function, 2016)

Laser stimulation of the acupoint ‘Zusanli’ (ST.36) on the radiopharmaceutical biodistribution in Wistar rats - Éric HFF Frederico; Ailton A Santos; Danúbia C Sá-Caputo; Rosane F Neves; Carlos AS Guimarães; Shyang Chang; Mario Bernardo-Filho (Journal of Biosciences, 2016)

Evaluation of a M-202 × Oryza nivara advanced backcross mapping population for seedling vigor, yield components and quality - Georgia C. Eizenga; Péricles C. F. Neves; Rolfe J. Bryant; Hesham A. Agrama; David J. Mackill (Euphytica, 2016)

Combining operational models and data into a dynamic vessel risk assessment tool for coastal regions - R. Fernandes; F. Braunschweig; F. Lourenço; R. Neves (Ocean Science, 2016)
The technological evolution in terms of computational capacity, data acquisition systems, numerical modelling and operational oceanography is supplying opportunities for designing and building holistic approaches and complex tools for newer and more efficient management (planning, prevention and response) of coastal water pollution risk events. A combined methodology to dynamically estimate time and space variable individual vessel accident risk levels and shoreline contamination risk from ships has been developed, integrating numerical metocean forecasts and oil spill simulations with vessel tracking automatic identification systems (AIS). The risk rating combines the likelihood of an oil spill occurring from a vessel navigating in a study area – the Portuguese continental shelf – with the assessed consequences to the shoreline. The spill likelihood is based on dynamic marine weather conditions and statistical information from previous accidents. The shoreline consequences reflect the virtual spilled oil amount reaching shoreline and its environmental and socio-economic vulnerabilities. The oil reaching shoreline is quantified with an oil spill fate and behaviour model running multiple virtual spills from vessels along time, or as an alternative, a correction factor based on vessel distance from coast. Shoreline risks can be computed in real time or from previously obtained data. Results show the ability of the proposed methodology to estimate the risk properly sensitive to dynamic metocean conditions and to oil transport behaviour. The integration of meteo-oceanic + oil spill models with coastal vulnerability and AIS data in the quantification of risk enhances the maritime situational awareness and the decision support model, providing a more realistic approach in the assessment of shoreline impacts. The risk assessment from historical data can help finding typical risk patterns (“hot spots”) or developing sensitivity analysis to specific conditions, whereas real-time risk levels can be used in the prioritization of individual ships, geographical areas, strategic tug positioning and implementation of dynamic risk-based vessel traffic monitoring.

Distribution of intermediate water masses in the subtropical northeast Atlantic - I. Bashmachnikov; Â. Nascimento; F. Neves; T. Menezes; N. V. Koldunov (Ocean Science, 2015)
This work presents the quantitative study of climatological distributions of mid-depth source water types in the northeast (NE) Atlantic using the optimum multiparameter analysis (OMP). It generalises a number of regional results from particular synoptic sections. The cores of the Mediterranean Water (MW), the modified Antarctic Intermediate Water (mAAIW) and the Subarctic Intermediate Water (SAIW) are detected and spatial variations of their depth/density are obtained: as expected, spreading of the water types is predominantly isopycnic and follows the major mid-depth circulation patterns. In some areas the turbulent transport also makes a considerable contribution. MW in the Atlantic spreads in three cores of different density: the upper MW core (northwest of the line 28° W, 35° N–14° W, 44° N) is found in the neutral density range of 27.65–27.70 kg m−3 at depths of 900–1000 m; the main MW core (between the line above and the line 35° W, 28° N–10° W, 37° N) has neutral density of around 27.75 kg m−3 and is found at 1000–1100 m; the lower MW core (southeast of the line 35° W, 28° N–10° W, 37° N) has neutral density of around 27.80 kg m−3 and is found at 1250–1350 m. The upper MW core has a comparatively low MW content (below 30 %) and is speculated to be transported by the mean flow from the northern Iberian Peninsula and the Bay of Biscay to the northern Azores. The main MW core contains the majority of the outflowing MW. It primarily originates from the Mediterranean undercurrent around Estremadura Promontory, where the Joint Effect of Baroclinicity and Bottom Relief (JEBAR) overrides the topographic β effect. It is transported west to the Azores Islands mostly along 39° N. The lower MW core originates in the Gulf of Cádiz, from where it is transported by the dominating flows southwestwards. The SAIW core is detected between 27.70 and 27.75 kg m−3. It is found to spread south along both slopes of the Mid-Atlantic Ridge (MAR). SAIW east of the MAR mixes with the upper and the main MW cores and re-circulates in a cyclonic gyre at 15–25° W and 34–39° N, penetrating as far south as the Azores Current. The mAAIW core is detected between 27.60 and 27.65 kg m−3. Its northernmost spreading limit is between 25 and 29° N, but its influence can be observed along the African coast and immediately west of the Canary Islands up to 32° N. The maximum concentration of the mAAIW core is found south of the Canary Islands, from where mAAIW is advected westwards, along with the westward spreading of the deep fraction of MW.

Selectivity of Organic Products to Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - J T Amaro; A F Bueno; A F Pomari-Fernandes; P M O J Neves (Neotropical Entomology, 2015)

Temperature–salinity distribution in the northeastern Atlantic from ship and Argo vertical casts - I. Bashmachnikov; F. Neves; Â. Nascimento; J. Medeiros; I. Ambar; J. Dias; X. Carton (Ocean Science, 2015)
The present study defines new interpolation functions for hydrological data. These functions are applied to generate climatological maps of temperature–salinity distribution with a 25 m depth interval and a 30 km space interval (MEDTRANS data set). The data undergo rigorous initial data quality control, having passed several filtering procedures. The gridding is done on neutral density surfaces, which allows better representation of thermohaline fronts for the same gridding radius. The multi-pass Barnes optimum interpolation procedure with spatially variable size of the gridding window is used. The shape of the window accounts for the dominant along-isobath direction of water mass transport over steeply sloping topography. A local ratio of topographic to planetary β-effects is used to define the shape of the window as a function of the relative importance of the topographic influence. The N/f ratio is applied to account for the baroclinic compensation decay of the topographic influence on water mass transport with the distance from the bottom. The gridded fields are available at the website of the Centre of Oceanography of the University of Lisbon (http://co.fc.ul.pt/en/data). The MEDTRANS climatology gives more details of the distribution of water characteristics in the subtropical northeastern Atlantic than other alternative climatologies and is able to reproduce a number of dynamic features described in the literature: the acceleration in the meanders of the Azores current; the cyclonic gyre in the Gulf of Cadiz; and the splitting and separation of the Mediterranean Water (MW) outflow in two veins near the Gorringe and Galicia banks. Seasonal climatologies, computed for the warm (May–October) and cold (November–April) seasons, reveal stronger zonal extension of the upper ocean patterns during the warm season, as compared to the cold one.

Mobility and persistence of the herbicide fomesafen in soils cultivated with bean plants using SLE/LTP and HPLC/DAD - Anna I. G. Costa; Maria Eliana L. R. Queiroz; Antônio A. Neves; Roberta C. de Assis; Carlos E. S. dos Soares; Antônio A. da Silva; Leonardo D’Antonino; André F. de Oliveira; Carlos R. Bellato (Environmental Science and Pollution Research, 2015)

A new species of Troglocarcinus (Decapoda: Brachyura: Cryptochiridae) symbiotic with the Brazilian endemic coral Mussismilia (Anthozoa: Scleractinia: Mussidae) - Roberta Canário; Marcelle F. S. Badaró; Rodrigo Johnsson; Elizabeth G. Neves (Marine Biology Research, 2015)

Is there a bottom-up cascade on the assemblages of trees, arboreal insects and spiders in a semiarid Caatinga? - L. Sousa-Souto; E. D. S. Santos; P. M. F. G. Figueiredo; A. J. Santos; F. S. Neves (Arthropod-Plant Interactions, 2014)

A Single Neurotoxic Dose of Methamphetamine Induces a Long-Lasting Depressive-Like Behaviour in Mice - Carlos D. Silva; Ana F. Neves; Ana I. Dias; Hugo J. Freitas; Sheena M. Mendes; Inês Pita; Sofia D. Viana; Paulo A. de Oliveira; Rodrigo A. Cunha; Carlos A. Fontes Ribeiro; Rui D. Prediger; Frederico C. Pereira (Neurotoxicity Research, 2014)

Comparative study of putative 9-cis-epoxycarotenoid dioxygenase and abscisic acid accumulation in the responses of Sunki mandarin and Rangpur lime to water deficit - D. M. Neves; M. A. Coelho Filho; B. S. Bellete; M. F. G. F. Silva; D. T. Souza; W. dos S. Soares Filho; M. G. C. Costa; A. S. Gesteira (Molecular Biology Reports, 2013)

Exploring the Multifactorial Nature of Autism Through Computational Systems Biology: Calcium and the Rho GTPase RAC1 Under the Spotlight - Fares Zeidán-Chuliá; José Luiz Rybarczyk-Filho; Alla B. Salmina; Ben-Hur Neves de Oliveira; Mami Noda; José Cláudio F. Moreira (NeuroMolecular Medicine, 2013)

Ants of Three Adjacent Habitats of a Transition Region Between the Cerrado and Caatinga Biomes: The Effects of Heterogeneity and Variation in Canopy Cover - F S Neves; K S Queiroz-Dantas; W D da Rocha; J H C Delabie (Neotropical Entomology, 2013)

Genetic Variability of Beauveria bassiana and a DNA Marker for Environmental Monitoring of a Highly Virulent Isolate Against Cosmopolites sordidus - D. V. Ferri; C. F. Munhoz; P. M. O. Neves; L. M. Ferracin; D. Sartori; M. L. C. Vieira; M. H. P. Fungaro (Indian Journal of Microbiology, 2012)

Diet and exercise training reduce blood pressure and improve autonomic modulation in women with prehypertension - Allan R. K. Sales; Bruno M. Silva; Fabricia J. Neves; Natália G. Rocha; Renata F. Medeiros; Renata R. T. Castro; Antonio C. L. Nóbrega (European Journal of Applied Physiology, 2012)

An operational model for the West Iberian coast: products and services - M. Mateus; G. Riflet; P. Chambel; L. Fernandes; R. Fernandes; M. Juliano; F. Campuzano; H. de Pablo; R. Neves (Ocean Science, 2012)
This paper presents the structure and application of a regional scale operational modelling tool for the West Iberian coast, and discusses its potential for products and services for both scientific and coastal management activities. The forecasting suite includes nested hydrodynamic models forced with up-to-date meteorological forecast data and large-scale model results. The present status of the system and its recent upgrades are reviewed, offering a general description of the main components of the system: the forcing data, the circulation model, the model outputs and the validation methodology of model results. Seasonal differences in temperature, salinity and current velocity fields are illustrated and show satisfactory reproduction of the top and deep layer thermodynamics. The system provides boundary forcing for a number of local-scale model applications via downscaling of the solution and enables potential products and services from which civil society will benefit.

Saving energy using fuzzy control applied to a chiller: an experimental study - F. V. Silva; J. E. Schmitz; L. C. Neves Filho; A. M. F. Fileti; V. Silveira Júnior (Clean Technologies and Environmental Policy, 2012)

Antioxidant treatment protects against matrix metalloproteinase activation and cardiomyocyte injury during acute pulmonary thromboembolism - Ozelia Sousa-Santos; Evandro M. Neto-Neves; Karina C. Ferraz; Carla S. Ceron; Elen Rizzi; Raquel F. Gerlach; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Losartan exerts no protective effects against acute pulmonary embolism-induced hemodynamic changes - Carlos A. Dias-Junior; Evandro M. Neto-Neves; Marcelo F. Montenegro; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Isolation of Cellulolytic Fungi from Waste of Castor (Ricinus communis L.) - Polyanna N. Herculano; D. M. M. Lima; M. J. S. Fernandes; R. P. Neves; C. M. Souza-Motta; A. L. F. Porto (Current Microbiology, 2011)

Influence of atypical pluviosity on phytoplankton assemblages in a stretch of a large sub-tropical river (Brazil) - Gilmar Perbiche-Neves; Mateus F. Ferrareze; Moacyr Serafim-Júnior; Madalena T. Shirata; Patrícia E. D. Lagos (Biologia, 2011)

Quercetin restores plasma nitrite and nitroso species levels in renovascular hypertension - Marcelo F. Montenegro; Evandro M. Neto-Neves; Carlos A. Dias-Junior; Carla S. Ceron; Michele M. Castro; Valeria A. Gomes; Alexandre Kanashiro; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Comparison of Biomass and Nutrient Dynamics Between an Invasive and a Native Species in a Mediterranean Saltmarsh - J. P. Neves; M. P. Simões; L. F. Ferreira; M. Madeira; L. C. Gazarini (Wetlands, 2010)

Assessing Seismic Damage Through Stochastic Simulation of Ground Shaking: The Case of the 1998 Faial Earthquake (Azores Islands) - G. Zonno; C. S. Oliveira; M. A. Ferreira; G. Musacchio; F. Meroni; F. Mota-de-Sá; F. Neves (Surveys in Geophysics, 2010)

Evaluation of metabisulfite and a commercial steel wool for removing chromium(VI) from wastewater - Caio F. Gromboni; George L. Donati; Wladiana O. Matos; Eduardo F. A. Neves; Ana Rita A. Nogueira; Joaquim A. Nóbrega (Environmental Chemistry Letters, 2010)

Brain and mind operational architectonics and man-made “machine” consciousness - Andrew A. Fingelkurts; Alexander A. Fingelkurts; Carlos F. H. Neves (Cognitive Processing, 2009)

Responses of talitrid amphipods to a gradient of recreational pressure caused by beach urbanization - V. G. Veloso; G. Neves; M. Lozano; A. Perez‐Hurtado; C. G. Gago; F. Hortas; F. Garcia Garcia (Marine Ecology, 2008)
Demands for public outdoor recreation and urbanization are a potential source of environmental disturbances, particularly on sandy beaches. These habitats have therefore experienced rapid degradation worldwide. Talitrid amphipods, which are common inhabitants of sandy beaches, are probably good indicators of such disturbances. In this study, we evaluated the responses of the two amphipods Talitrus saltator and Atlantorchestoidea brasiliensis to human pressure on Spanish and a Brazilian beach, hypothesizing that disregarding species differences, their population sizes will decline under urbanized conditions. The Barra da Tijuca (Brazil) and Levante (Spain) beaches have mixed landscapes with varying levels of development, and each has a protected area (MPA) adjacent to urbanized sites. Numbers of talitrids as well as visitors were compared among sites on each beach. Talitrids were most abundant at the protected sites. This was true of both beaches, even though temporal patterns of human activity were quite different, with Levante experiencing sharp declines in the number of visitors during its harsh winter. Urbanized sites did not experience high Talitrid densities even during a period of low human pressure. On this basis, T. saltator and A. brasiliensis were considered good indicators of urbanization and recreational activities on sandy beaches. MPAs were found to be very important for the successful conservation of the talitrid populations. A feasible method of managing human pressure and thereby conserving beach biodiversity therefore seems to be the establishment of beach MPAs.

Toxicity Evaluation to Mice of Phylloseptin-1, an Antimicrobial Peptide from the Skin Secretion of Phyllomedusa hypochondrialis (Amphibia) - Selma Kückelhaus; José Roberto S. A. Leite; Mateus P. Neves; Karla S. Frota; Lídia F. Abdala; Maria Imaculada Muniz-Junqueira; Carlos Bloch; Carlos Eduardo Tosta (International Journal of Peptide Research and Therapeutics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Modelling the influence of nutrient loads on Portuguese estuaries - Sofia Saraiva; P. Pina; F. Martins; M. Santos; F. Braunschweig; R. Neves (Hydrobiologia, 2007)

Primary production and nutrient content in two salt marsh species,Atriplex portulacoides L. andLimoniastrum monopetalum L., in Southern Portugal - J. P. Neves; L. F. Ferreira; M. P. Simões; L. C. Gazarini (Estuaries and Coasts, 2007)

Effects of Cu, Ni and Zn on Lettuce Grown in Metal-Enriched Vermicompost Amended Soil - C. P. Jordão; L. L. Fialho; P. R. Cecon; A. T. Matos; J. C. L. Neves; E. S. Mendonça; R. L. F. Fontes (Water, Air, & Soil Pollution, 2006)

The Association of Two Gall Crabs (Brachyura: Cryptochiridae) with the Reef-building Coral Siderastrea stellata Verrill, 1868 - R. Johnsson; E. Neves; G. M. O. Franco; F. L. da Silveira (Hydrobiologia, 2006)

Contribution of biological nitrogen fixation to cowpea: a strategy for improving grain yield in the semi-arid region of Brazil - L. M. V. Martins; G. R. Xavier; F. W. Rangel; J. R. A. Ribeiro; M. C. P. Neves; L. B. Morgado; N. G. Rumjanek (Biology and Fertility of Soils, 2003)

Body shape and size divergence among populations of Poecilia vivipara in coastal lagoons of south‐eastern Brazil - F. M. Neves; L. R. Monteiro (Journal of Fish Biology, 2003)
Geometric shape analyses were used to study body shape and size variation among populations of the livebearing fish Poecilia vivipara inhabiting the recently formed coastal lagoons of Grussaí and Iquipari in Northern Rio de Janeiro State, Brazil. The largest components of morphological variation among females were between different habitats in the same lagoon, whereas for males there were larger differences between lagoons than between habitats. The shape differences were mostly localized in the head region and midbody, which indicated different patterns of locomotion and foraging behaviour optimized for the habitat experienced by each population. The pattern of size variation was similar to that of size‐independent shape variation.

Micropropagation of endangered endemic Brazilian bromeliad Cryptanthus sinuosus (L.B. Smith) for in vitro preservation - R. Arrabal; F. Amancio; L.A. Carneiro; L.J. Neves; E. Mansur (Biodiversity and Conservation, 2002)

Simulating vertical water mixing in homogeneous estuaries: [2pt] the SADO Estuary case - F. Martins; P. Leitão; R. Neves (Hydrobiologia, 2002)

Growth response of coffee tree shoots and roots to subsurface liming - Luciana Aparecida Rodrigues; Herminia E.P. Martinez; Julio Cesar L. Neves; Roberto F. Novais; Sebastião M. Mendonça (Plant and Soil, 2001)

Induction and inhibition of human lymphocyte transformation by the lectin from the red marine alga Amansia multifida - Hermenio C. Lima; Francisco H. F. Costa; Alexandre H. Sampaio; Samya A. Neves; Norma M. B. Benevides; Darlio I. A. Teixeira; David J. Rogers; Ana Lúcia P. Freitas (Journal of Applied Phycology, 1998)